Experience of Partnership with Fistula Program in Bangladesh: University Fistula Center, Bangabandhu Sheikh Mujib Medical University - Alam, Farhana; Chowdhury, Saleha Begum; Mahmud, Sharmeen (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The aim of this paper is to share the performance data of University Fistula Center (UFC), BSMMU as well as the partnership experience of UFC with national fistula program at different levels and various activities. Methods: UFC uses an aggregated DHIS2 database and Safe Surgery Toolkit, two dedicated systems for record keeping of fistula activities introduced by the Fistula Care Plus (FC+) project at EngenderHealth. UFC fistula service data have been compiled using DHIS2 and SPSS. Results: From 2015 to 2018, UFC has provided surgical care to 98 cases fistula and 72 cases of complete perineal tear. UFC has provided technical assistance in field testing of the 4Q checklist- a novel tool for fistula case identification at the field level developed and refined by the FC+ project. UFC has contributed developing and testing a model for Community Based Fistula Diagnosis events (CFDEs) and to drafting the 2nd national fistula strategy of Bangladesh. Conclusions: The UFC is now recognized as a key contributor to national fistula programming in Bangladesh and in defining standards of care.